Essential fatty acids deficient diet modulates N-Acylethanolamide profile in rat's tissues. (February 2020) - Carta, Gianfranca; Murru, Elisabetta; Vargiu, Romina; Collu, Maria; Carta, Manolo; Banni, Sebastiano; Stancampiano, Roberto
Highlights: A diet deficient of essential fatty acids, induced a reduction of anandamide and palmitoylethanolamide in liver and brain, and a significant increase of oleoylethanolamide in liver and adipose tissue. The enhanced biosynthesis and deposition of oleic acid, induced by essential fatty acids deficiency, was associated to a higher oleioleoylethanolamide concentrations in liver and adipose tissue. Changes in tissue N-acylethanolamide profile may contribute to body weight reduction distinctive of essential fatty acids deficiency. The enhanced biosynthesis and deposition of oleic acid, induced by essential fatty acids deficiency, was associated to a higher oleioleoylethanolamide concentrations in liver and adipose tissue. Abstract: No data are available on whether a diet deficient of the essential fatty acids is able to modulate tissue levels of endocannabinoids and congeners. Male rats fed for 12 weeks a diet deficient of essential fatty acids, palmitic and oleic acids (EFAD), replaced with saturated fatty acids (SAFA), showed lowered n-3 and n-6 PUFAs levels in plasma, liver and adipose tissue, with concomitant steep increase of oleic and mead acids, while in hypothalamus no changes in PUFA concentration were detected and only palmitoleic acid was found increased. We found a reduction of anandamide and palmitoylethanolamide in liver and brain, while oleoylethanolamide increased significantly in liver and adipose tissue, associated to a 50 % body weight decrease. Changes in N-acylethanolamide profile may contribute to body weight reduction distinctive of EFA deficiency.